Dietary Polyphenol Intake, Blood Pressure, and Hypertension: A Systematic Review and Meta-Analysis of Observational Studies - Justyna Godos; Marilena Vitale; Agnieszka Micek; Sumantra Ray; Daniela Martini; Daniele Del Rio; Gabriele Riccardi; Fabio Galvano; Giuseppe Grosso (MDPI AG, 2019)
Background: Dietary polyphenols, including flavonoids, have been the focus of major recent attentions due to their wide content in a variety of foods commonly consumed and the findings from numerous studies showing evidence of an association with positive outcomes on human health. Methods: A systematic search using electronic databases PubMed and EMBASE was performed to retrieve English language studies published from the earliest indexing year of each database to April 2019, reporting on the association between dietary flavonoids intake and hypertension. Results: The search strategy resulted in the final selection of 20 studies including 15 cross-sectional investigations and 7 prospective cohorts (1 study reported on 3 prospective cohorts). 5 prospective cohorts, comprising 200,256 individuals and 45,732 cases of hypertension were included in the quantitative analysis. Analysis by extreme quantiles of intake of flavonoid showed a non-significant association with decreased risk of hypertension (RR (risk ratio): 0.96, 95% CI (confidence interval): 0.89, 1.03). Taking into consideration individual flavonoid subclasses, dietary anthocyanins intake was associated with 8% reduction in risk of hypertension, when comparing highest vs. lowest exposure (RR: 0.92, 95% CI: 0.88, 0.97). Conclusions: Further studies are needed to strengthen the retrieved association between anthocyanins consumption and decreased risk of hypertension and clarify whether total flavonoids or rather individual subclasses may exert beneficial effects on blood pressure.